Gas Sensors: High‐Performance, Transparent Thin Film Hydrogen Gas Sensor Using 2D Electron Gas at Interface of Oxide Thin Film Heterostructure Grown by Atomic Layer Deposition (Adv. Funct. Mater. 7/2019). (12th February 2019) - Kim, Sung Min; Kim, Hye Ju; Jung, Hae Jun; Park, Ji‐Yong; Seok, Tae Jun; Choa, Yong‐Ho; Park, Tae Joo; Lee, Sang Woon
Abstract : In article number1807760, Tae Joo Park, Sang Woon Lee, and co‐workers develop a high‐performance, transparent, and extremely thin (<15 nm) hydrogen gas sensor using 2D electron gas at the interface of an Al2 O3 /TiO2 thin film heterostructure grown by atomic layer deposition. This extremely thin gas sensor can be fabricated on a flexible substrate, enabling the development of flexible gas sensors.